18 Downstream investigation of non-cardiac incidental findings in patients undergoing ct coronary angiography: findings from the multi-centre randomised controlled scot-heart trial. (18th May 2017) - Williams, Michelle C; Hunter, Amanda; Shah, Anoop; Dreisbach, John; McCaull, Jonathan Weir; Macmillan, Mark; Kirkbride, Rachel; Baird, Andrew; Hawke, Fiona; Mirsadraee, Saeed; Beek, Edwin van; Newby, David E; et al.
Abstract : Introduction: Non-cardiac findings can be identified on computed tomography coronary angiography (CTCA). We assess the follow-up of non-cardiac incidental findings, and impact of changes in lung nodule follow-up guidelines. Methods: This sub-study of the SCOT-HEART randomised controlled trial assessed images and health records of patients who underwent CTCA. Non-cardiac incidental findings were classified as the cause of symptoms (yes, probable, unlikely, no) and significant findings were those requiring further investigation, follow-up or treatment. Recommendations for lung nodule follow-up were provided as per 2005 Fleischner guidelines. We assessed potential changes using the 2015 British Thoracic Society (BTS) guidelines and 2017 Fleischner guidelines. Results: CTCA was performed in 1778 patients and non-cardiac findings were identified in 677 (38%). 173 (10%) were defined as significant and 22 (1.2%) were the cause of symptoms. Lung nodules, masses or granuloma were identified in 200 (11%). Follow-up imaging for lung nodules was recommended for 126 patients (7%) but performed in 85 (4.7%). Malignancy was subsequently diagnosed in 7 (0.4%). Using 2016 BTS guidelines would mean 68 fewer scans in 47 patients and the 2017 Fleischner guidelines would mean 78 fewer scan in 53 patients. None of these developed malignancy. Applying the 2016 BTS guidelines would mean a 50% cost saving and the 2017 Fleischner guidelines would mean a 57% cost saving. Conclusion: Significant non-cardiac findings are uncommon, but may represent an important treatable cause of chest pain. New guidelines for lung nodule follow-up will reduce the number CT scans required, without the risk of missing malignancy.